DINED (Delivery‐related INjuries in the Emergency Department) part 2: A chart review of risk factors and injuries affecting food delivery riders. (11th April 2022) - Bertenshaw, Claire; Mitchell, Gary; McKinlay, Andrew; Cameron, Cate; Vallmuur, Kirsten; Smyth, Tanya; Witts, Morgan
Abstract: Objective: This study aimed to examine patterns of injury, the impact of these injuries on patients and identification of potentially modifiable contributing factors through industry regulation reforms and education. Methods: Food delivery rider (FDR)‐related presentations to the Royal Brisbane and Women's Hospital Emergency and Trauma Centre for a year from September 2020 were identified. Data collected included patient and incident demographics: time, type and location of injuries, investigations and care required, length of stay, admission requirements and follow up. Results: The cohort included 81.8% male with a mean age of 25.2 years. Most injuries occurred on the road from a collision with a vehicle. The most common injury was fractures. Incidence increased on weekends and during the evening. More than half the cohort were admitted to hospital. Only 22.7% of patients were eligible for workers compensation and less than half were covered by Medicare. The majority (72.7%) of cases involved non‐resident riders from other countries. Conclusion: The majority of FDRs presenting with injuries are not Australian citizens and less than half were Medicare eligible potentially contributing to inadequate access to care especially fracture follow up. There were spikes in injuries occurring at night, weekends and during periods of pandemic associated lockdowns demonstrating an increased usage of delivery services during these times. Results highlight injury patterns experienced by delivery riders and potentially modifiable risk factors for this rapidly growing area of employment within the gig economy. Abstract : There has been a recent surge in the use of food delivery riders (FDRs) in metropolitan areas. This has come with an increased presentation of this vulnerable cohort with work‐related injuries to the EDs servicing inner city areas. The present study aimed to further explore the distinct rider‐related, work‐related and environmental factors that may influence food delivery accidents.